Climate change, food security and environmental securi-ty : A conflict inclination assessment of Karamoja region of Uganda - Akiyode, Oluwole; Tumushabe, Anne; Hadijjah, Katongole; Peter, Onu (International Journal of Scientific World, 2017)
The study investigates the consequences of climate change on food security and environmental security in the Karamoja region of Uganda. It relates climate change to the conflict, insecurity and crises that have been witnessed in the region in the past years.It examines the implications of the change in the grazing pattern of the pastoralists and herdsmen in the time of recurrent drought and dry spells in Karamoja on the security of the region and other communities in Uganda and beyond. It relates the interplay of climate change, environmental security and food security to human security in Karamoja region.It also through focus group discussion (FGD) conducted in Kaabong District of the Karamoja region, identifies the presumed impacts of climate change on the environment and the people alongside its socio-economic implications. In the end, the study suggests proactive environmental security programmes in the Karamoja region which are expected to encourage sustainable mitigation and adaptation strategies in its communities, which will encourage its regional peace, security and stability.